Impact of Bee Pollen Supplementation on Growth Performance, Blood Parameters, Antioxidant Status, And Immune Response in Quail - Jamal A. Embark (African Journal of Advanced Pure and Applied Sciences, 2025)
The objective of the study was to assess the impact of pollen supplementation (BP) on the growth performance, certain hematological parameters, antioxidant capacity, and immune response of Japanese quail throughout the growth phase (7-42 days). A total of 270 Japanese quail chicks, aged 7 days, were allocated into three experimental groups (90 birds per treatment) with three replicates (30 birds per replicate). The chicks were classified into three treatment groups as follows: T1: received a basal diet devoid of any additives (control), while T2 and T3 were administered a basal diet augmented with 4 g and 8 g of pollen per kg of diet, respectively. The outcomes of the statistical evaluation revealed that variations in the weight of the quail commenced at 21 days of age and persisted until the conclusion of the study at 42 days. The body weight recorded at the end of the experiment was significantly greater than that of the quails that did not receive bee pollen (control group), and indicated a notable increase in the levels of total protein, albumin, globulin, and glucose in diets containing bee pollen. The findings suggested that the total weight gain of the quails exhibited considerable improvement in the two supplemented treatments following the second week of the experiment, and there were no significant disparities in the coefficients regarding feed consumption rates. Conversely, the impact of supplementation on the cholesterol levels in the quail’s blood was pronounced, as there was a decrease observed in the two supplemented treatments; furthermore, a significant reduction in the total lipid levels of the supplemented group was noted in comparison to the control group. Additionally, the results indicated that the diets enriched with bee pollen did not exert a significant influence on the concentrations of the enzymes AST and ALT in the serum. A marked decrease in the concentration of MDA was observed, concluding that the incorporation of bee pollen enhanced the performance, certain hematological parameters, antioxidant status, and immune response of the Japanese quail.